Role of risk of malignancy index 4 in evaluation of adnexal masses - Kaur, Amarjeet; Sharma, Sujata; Singh, Sohan (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: The discrimination between benign and malignant adnexal masses is important for clinical management and surgical planning in such patients. Various combined methods of evaluation adnexal mass have also been proposed. Risk of malignancy index (RMI) is a combined parameter which is simple, preclinical and highly sensitive, and more specific. Risk of malignancy index 4 (RMI 4) is calculated as a product of ultrasound score (U)×menopausal score (M)×CA 125×tumor size. Objective of this study was to determine if the RMI (RMI 4) can distinguish between benign and malignant adnexal masses. Methods: A prospective study was conducted on 30 women with an adnexal mass presenting in the OPD and emergency and RMI-4 calculated. Cut off level of 450 was set to differentiate between benign and malignant mass. Results: In this study, the value of RMI-4 is less than 450 in 17 patients with benign disease and 3 patients with malignant disease. The value is more than 450 in 2 patients with benign disease and 8 patients with malignant disease. RMI-4 >450 had a sensitivity of 72.73% and specificity is 89.47%. The positive predictive value is 80% and negative predictive value is 85%. The p-value for RMI-4 in this study is 0.001 which is highly significant. Conclusions: RMI is a reliable, simple, easy to use and cost-effective method in differentiating benign from malignant adnexal masses.